Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3354/cr01317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate and historical adaptation measures on barley yield trends in Finland

Abstract: In this study, the WOFOST crop simulation model was used together with comprehensive empirical databases on barley Hordeum vulgare L. to study the contributions of different yield-determining and -limiting factors to observed trends of barley yield in Finland from 1988 to 2008. Simulations were performed at 3 study sites representing different agro-ecological zones, and compared with the data from experimental sites and that reported by local farmers. Yield gaps between simulated potential yields and farmers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, this adaptation in the choice of varieties planted and in management is likely also to contribute to generally lower yields. A study by Olesen et al (2011) seems to support this argument, showing that in Finland, a small yield increase has occurred during the last 10−20 yr that is partly linked to increasing temperatures, which has allowed earlier sowing and a prolonged growing season (Rötter et al 2013, Peltonen-Sainio & Jauhiainen 2014, Palosuo et al 2015. On the other hand, the wheat yields in Greece have been declining, which is likely also linked to the increase in temperatures.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, this adaptation in the choice of varieties planted and in management is likely also to contribute to generally lower yields. A study by Olesen et al (2011) seems to support this argument, showing that in Finland, a small yield increase has occurred during the last 10−20 yr that is partly linked to increasing temperatures, which has allowed earlier sowing and a prolonged growing season (Rötter et al 2013, Peltonen-Sainio & Jauhiainen 2014, Palosuo et al 2015. On the other hand, the wheat yields in Greece have been declining, which is likely also linked to the increase in temperatures.…”
Section: Discussionmentioning
confidence: 53%
“…The stagnating wheat (and barley) yields across European regions (as depicted in Fig. 3) have been found to be co-determined by the warming climate (Brisson et al 2010) and/or by changes in management, especially in the changes to fertilization application due to environmental regulations (Finger 2010, Palosuo et al 2015. Gömann et al (2015) reported that wheat crops have been extended to less favorable sites during the last decades in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding on climate impacts and adaptations of crop growth and productivity can be accelerated by analyzing historical experiences over the past few decades (Tao et al, 2012a,b;Palosuo et al, 2015). Along this line, recently, an increasing number of studies have investigated climate impacts on crop yields in a range of regions of the world using statistical models and long-term historical datasets of crop and climate (e.g., You et al, 2009;Reidsma et al, 2009;Welch et al, 2010;Lobell et al, 2011a;Tao et al, 2012b;Ray et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Historical crop trial data, with accurate records of phenology, yield, weather, as well as cultivars and management practices, allow one to study how weather affects crop yield in a setting in which known agronomic management practices are taken based on actual weather (Welch et al, 2010;Lobell et al, 2011b;Tao et al, 2012a;Palosuo et al, 2015). Such diagnostic studies are more robust in understanding impact and adaptation mechanisms, improving crop models, and consequently have important implications for predicting the impact of future climate change on agricultural production (Welch et al, 2010;Lobell et al, 2011b;Tao et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished by reducing the gaps between farmers' actual crop yields and such yields that would be possible if optimal management were adopted, the so-called 'yield gap' (Yg, Van Ittersum et al, 2013). Assessment of the scope for narrowing these gaps relies on a robust reference database on yield gaps and their underlying causes (Van Bussel et al, 2015;Palosuo et al, 2015). Over the last two decades a number of different methods for yield gap analysis have been developed (see, e.g.…”
Section: Scope and Need For Technological Innovationmentioning
confidence: 99%